Pembuatan Teh Herbal dari Bunga Telang (clitoria ternatea l) Dengan Variasi Penambahan Lemon (citrus limon l) Untuk Uji Antioksidan - Zhahyra, Tashania; Deffia Aryati Putri; Dzakma Putri Alsa; Ghina Khairiyah; Della Rosalynna Stiadi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Bunga telang (Clitoria ternatea L.) also known as blue pea, is a distinctive flower with single petals, that come in purple, blue, pink, and whote color. This flower is widely used as a natural colorant due to its high anthocyanin content, lemon juice was added to butterfly pea flower to determine antioxidant activity based on the number of hydroxyl groups capable of donating hydrogen atoms to free radical compounds. The color change observed is influenced by the acidity level (pH) of the beverage. Lemon contains a high amount of citric acid, which can flower the pH of the butterfly peaextract solution. The colot change from blue to purple, redpr even pink indicates reaction anthocyanins to pH changes. Antioxidant activity was teste using the DPPH ( 2,2-diphenyl-picrylhydrazil) method, which measueres the samples ability to scavenge free radical. The lower the IC 150 value obtained, the stronger the antioxidant capacity of the substance. The results showed that the water content in butterfly pea tea was 15,5% and total ash content in butterfly and total ash content was 8%. The IC 50 value obtained was 53,65 which is classified as very strong in antioxidant activity and shows great potential as a natural antioxidant source